Diagnostic Value of MicroRNAs for Urologic Cancers: A Systematic Review and Meta-Analysis. Issue 37 (September 2015) - Ouyang, Hui; Zhou, Yanzhao; Zhang, Li; Shen, Guanxin
Abstract : Supplemental Digital Content is available in the text Abstract : Abstract: MicroRNAs (miRNAs), particularly those extracted from the blood or tissues, have become the focus of urologic cancers research. However, the literature reviews on the accuracy of miRNA detection in urologic cancers have been inconsistent, leading us to perform this meta-analysis. Eligible studies were searched in PubMed and other databases. To calculate the pooled detection accuracy estimates, we used a bivariate random-effects meta-analysis model. According to the exclusion and inclusion criteria, 41 studies were included. Overall, the results showed sensitivity of 0.77 (95% CI: 0.74–0.80) and specificity of 0.76 (95% CI: 0.72–0.79), with an area under the SROC curve (AUC) of 0.83 (95% CI: 0.80–0.86). In addition, further subgroup analyses were also conducted. Firstly, the multiple miRNAs subgroup has significantly better diagnostic specificity than single miRNA subgroup among all these cancer types, while only bladder cancer (BC) and prostate cancer (PC) group with significantly greater diagnostic sensitivity with their multiple miRNA detection. Secondly, none of these cancer types showed significant differences on diagnostic sensitivity and specificity in their specimen and sample size subgroups. Thirdly, the diagnostic sensitivity between Asian (0.791, 95% CI: 0.748–0.827) and Caucasian (0.713, 95% CI: 0.666–0.756) in BC type was shown significant different with the P -value of 0.011. The results of our study suggested that miRNAs, particularly the multiple miRNAs, may play an important role in diagnosis and monitoring of the urologic cancers as superior biomarkers.